2014
DOI: 10.3748/wjg.v20.i33.11815
|View full text |Cite
|
Sign up to set email alerts
|

Non invasive blood flow measurement in cerebellum detects minimal hepatic encephalopathy earlier than psychometric tests

Abstract: Non invasive BF determination in cerebellum using ASL may detect MHE earlier than the PHES. Altered NO-cGMP pathway seems to be associated to altered BF in cerebellum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…Interestingly, the cerebellar blood flow is increased in cirrhotic patients, and specifically elevated in the vermis of MHE group. These alterations in blood flow correlate negatively with the execution of the NCT-A and B of PHES [6]. Alterations in GM volume in cerebellum, along with alterations in blood flow, could explain the impairment in executive function and cognitive processing speed in patients evaluated through the performance of such PHES subtests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the cerebellar blood flow is increased in cirrhotic patients, and specifically elevated in the vermis of MHE group. These alterations in blood flow correlate negatively with the execution of the NCT-A and B of PHES [6]. Alterations in GM volume in cerebellum, along with alterations in blood flow, could explain the impairment in executive function and cognitive processing speed in patients evaluated through the performance of such PHES subtests.…”
Section: Discussionmentioning
confidence: 99%
“…Around 33–50% of cirrhotic patients without clinical symptoms of HE show minimal hepatic encephalopathy (MHE) with mild cognitive impairment, attention deficits [3,4] and impaired visuo-motor and bimanual coordination [5, 6]. MHE decreases the quality of life, and increases the probability of suffering HE [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Felipo et al found that determining noninvasive brain blood flow using arterial spin labeling (ASL) could detect MHE earlier than Psychometric Hepatic Encephalopathy Score (PHES) [32] indicating there are early changes to cerebral hemodynamics in the preliminary stages of HE. In the present study, prior to treatment, we observed no differences in V p ( P = 0.356) of right MCA, while significant differences were evident in V m , V d , PI, and RI ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…39 We have previously shown that cerebral blood flow, measured by arterial spin labelling, is increased selectively in the cerebellar vermis and reduced in the occipital lobe in patients with MHE compared with patients without MHE, and that blood flow in cerebellar vermis is predictive for MHE. 40 These alterations could contribute to impairment in postural control of patients with MHE. Hyperammonaemia acts synergistically with inflammation to induce MHE.…”
Section: Discussionmentioning
confidence: 99%